Kompetensi Juru Dakwah dalam Pandangan Jama’ah Tabligh - Muhammad Azizullah Ilyas (Jurnal Dakwah dan Komunikasi, 2017)
The movement of dawah Tablighi Jamaat has been going on almost all regions of Indonesia even worldwide, this can be seen from the scope of the movement of Tablighi Jamaat cross-country, but in practice there is often a friction between the da’i of Tablighi Jamaat and society that can be observed from some village or mosques that reject the presence of Tablighi Jamaat, it is necessary to know how the actual concept of dawah competence according to Tablighi Jamaat and how the effort Tablighi Jamaat do in foster da’i that will be work In the community. This study uses an analytical descriptive approach and combines library studies, participant observation and interviews. The study found that Tablighi Jamaat has several references and competencies that must be possessed by da’i, there are thirteen major competencies that are termed with the ‘character of dai’. This competence is support the development of dawah, but in the field, found that many members of Tablighi Jamaat not understand the intent of these 13 characters and some of them have not applied this competence in dawah, in fact members of Tablighi Jamaat not be required to be good first before joining in dawah aktivity, this opinion based on to the hadith of the prophet “conver from me, even if it is one verse”.